2018
DOI: 10.1155/2018/2569129
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Study of (5-Nitroheteroaryl-1,3,4-Thiadiazole-2-yl) Piperazinyl Derivatives to Predict New Similar Compounds as Antileishmanial Agents

Abstract: To search for newer and potent antileishmanial drugs, a series of 36 compounds of 5-(5-nitroheteroaryl-2-yl)-1,3,4-thiadiazole derivatives were subjected to a quantitative structure-activity relationship (QSAR) analysis for studying, interpreting, and predicting activities and designing new compounds using several statistical tools. The multiple linear regression (MLR), nonlinear regression (RNLM), and artificial neural network (ANN) models were developed using 30 molecules having pIC50 ranging from 3.155 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Quantum descriptors have been calculated to describe the electronic structure of the studied molecules in order to predict their reactivity toward the external environment, and consequently, these descriptors will provide useful information to explain the studied activity. We adopted DFT theory with (B3LYP/ 6‐31G [p, d]) basis to calculate the quantum descriptors based on some comparative QSAR studies having demonstrated that this theory lead to reliable and accurate results 51–53 . The descriptors values of the studied structures are presented in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum descriptors have been calculated to describe the electronic structure of the studied molecules in order to predict their reactivity toward the external environment, and consequently, these descriptors will provide useful information to explain the studied activity. We adopted DFT theory with (B3LYP/ 6‐31G [p, d]) basis to calculate the quantum descriptors based on some comparative QSAR studies having demonstrated that this theory lead to reliable and accurate results 51–53 . The descriptors values of the studied structures are presented in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results of the electric dipole moment values determined by the B3LYP/6-311++G­(d,p) method were consistent with previous studies on organic compounds with mosquito-repellent activity. , The calculated values of the electric dipole moment, HOMO and LUMO energies, and Mulliken charge on the N atoms and ring, logP: octanol–water partition coefficient are presented in Table S2. The results showed that the electric dipole moment values of compounds 4a – 4i ranged from 1.178 to 8.059 D, with the highest value observed for compound 4i , which contains the para -substituted NO 2 group with the lowest HOMO energy value of −7.026 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The DFT method was employed to investigate the ground-state geometry of the studied compounds. The B3LYP function and the 6-311++g­(d,p) set of basis functions were used in the optimization process using the G09 software. , The optimized structures were analyzed to determine the compound’s energy, charge properties, and vibrational frequencies. The optimization is successful if the optimized structure contains no imaginary frequencies and meets the convergence criteria of the G09 program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in more than 90 countries in Africa, the Americas, and Asia, and it is considered a severe epidemic in several African countries, namely in North, Central, and East Africa, and the Horn of Africa. 1 The parasite is transferred to the human host by the bites of sandflies of the genera Phlebotomine and Leutzomia. 2 Leishmaniasis has infected around 12 million people, resulting in 0.5 million visceral cases and 1.5–2 million instances of cutaneous illness.…”
Section: Introductionmentioning
confidence: 99%